Entrepreneurial Behaviours of Farm Women from Baghpat District, Uttar Pradesh - Singh, Shivani; Singh, Premlata; Satyapriya, (Indian Journal of Extension Education, 2018)
Providing food security has been focus of the Government’s planning and policy. Food security means availability of sufficient foodgrains to meet the domestic demand as well as access, at the individual level, to adequate quantities of food at affordable prices. Attainment of self-sufficiency in foodgrains production at the national level has been one of the major achievements of the country. Addressing food security cannot only be done by creating awareness about nutrition and healthy food, capacity building interventions but to take it to another level an entrepreneurial approach is highly recommended. Global changes have created economic opportunities and women entrepreneurs have emerged as a distinct class. Their contribution to national economy is now substantial. Women entrepreneurship directly or indirectly decides the Nation’s economy and its growth, In India the development in women entrepreneursnip had come a long way since it was systematically initiated in early 80s.To understand the attitude and acceptance of farm women this inline study was conducted in Mukari and Lehchhoda villages of Baghpat district Uttar Pradesh with 60 farm women. The results revealed that two third (58.33%) of farm women belongs to medium entrepreneurial behavior.Socio economic factors such as : Education, land holding, annual income, economic motivation and attitude towards value addition of agricultural produce and business aspect in agri-nutri food products shows positive and only information found negatively significant relationship with entrepreneurial behaviour. Whereas other variables like interest in learning and soci-economic status has been studied.
Keywords: Entrepreneurial Behaviour; farm women and nutripreneur